Genetic linkage map of Chinese native variety faba bean (Vicia faba L.) based on simple sequence repeat markers. Issue 4 (7th June 2013) - Ma, Yu; Bao, Shi‐ying; Yang, Tao; Hu, Jin‐guo; Guan, Jian‐ping; He, Yu‐hua; Wang, Xue‐Jun; Wan, Yu‐ling; Sun, Xue‐lian; Jiang, Jun‐ye; Gong, Cui‐xiang; Zong, Xu‐xiao; et al.
Abstract Simple sequence repeat (SSR) marker is a powerful tool for construction of genetic linkage map which can be applied for quantitative trait loci (QTL) and marker‐assisted selection (MAS). In this study, a genetic map of faba bean was constructed with SSR markers using a 129 F2 individuals population derived from the cross of Chinese native variety 91825 (large seed) and K1563 (small seed). By screening 11 551 SSR primers between two parents, 149 primer pairs were detected polymorphic and used for F2 population analysis. This SSR‐based genetic linkage map consisted of 15 linkage groups with 128 SSR. The map encompassed 1587 cM with an average genetic distance of 12.4 cM. The genetic map generated in this study will be beneficial for genetic studies of faba bean for identification of marker‐locus‐trait associations as well as comparative mapping among faba bean, pea and grasspea.